CROWDFUNDING IN ENTREPRENEURIAL SYSTEM. TYPES AND TECHNOLOGIES - S. Rukavishnikov (Вестник университета)
The work is dedicated to innovative ways of attracting funding - crowdfunding. Crowdfunding is seen as an investment and investing instrument. It highlights the advantages of the new tool. The article describes the types of crowdfunding, which entrepreneurs use to attract funding for projects, as well as highlights of their nature, and advantages, there is a classification of crowdfunding forms of investment. We investigated some internet-sites that specialize in one or another form of crowdfunding. A comparative analysis of crowdfunding forms, in order to present the main differences in the motivation of potential investors. It describes the motivational component of investors to commit investments.